Error-Driven Retrieval in Agreement Attraction Rarely Leads to Misinterpretation - Schlueter, Zoe; Parker, Dan; Lau, Ellen (Frontiers in Psychology, 2019)
Previous work on agreement computation in sentence comprehension motivates a model in which the parser predicts the verb’s number and engages in retrieval of the agreement controller only when it detects a mismatch between the prediction and the bottom-up input. It is the error-driven second stage of this process that is prone to similarity-based interference and can result in the illusory licensing of a subject-verb number agreement violation in the presence of a structurally irrelevant noun matching the number marking on the verb (‘The bed by the lamps were…’), giving rise to an effect known as ‘agreement attraction’. Here we ask to what extent the error-driven retrieval process underlying the illusory licensing alters the structural and thematic representation of the sentence. We use a novel dual-task paradigm that combines self-paced reading with a speeded forced choice task to investigate whether agreement attraction leads comprehenders to erroneously interpret the attractor as the thematic subject, which would indicate structural reanalysis. Participants read sentence fragments (‘The bed by the lamp/lamps was/were undoubtedly quite’) and completed the sentences by choosing between two adjectives (‘comfortable’/’bright’) which were either compatible with the subject’s head noun or with the attractor. We found the expected agreement attraction profile in the self-paced reading data but the interpretive error occurs on only a small subset of attraction trials, suggesting that in agreement attraction agreement checking rarely matches the thematic relation. We propose that illusory licensing of an agreement violation often reflects a low-level rechecking process that is only concerned with number and does not have an impact on the structural representation of the sentence. Interestingly, this suggests that error-driven repair processes can result in a globally inconsistent final sentence representation with a persistent mismatch between the subject and the verb.